(untitled) (Research, Society and Development, 2020)
Since the late twentieth century, there has been discussion about the insertion of Modern and Contemporary Physics (MCP) in Basic Education. Considering the current panorama of discussions about the need for these subjects to be present in everyday school life, more precisely in high school (HS), this research aims to investigate the conceptions of physics teachers of Sobral public schools about the teaching of MCP in your HS classes. For this, a semi-structured questionnaire was applied to all physics teachers of the Sobral public schools who completed their graduation after 2002. It was observed that the time, the curriculum of this level and the absence of these subjects in the entrance exams are the main obstacles pointed out by the students. teachers to teach them and that 67% claim to insert MCP in their classes, as well as draw attention to the need for new methodologies for teaching these contents in HS and 47% had difficulties in these subjects during their training.